2018
DOI: 10.1002/term.2667
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy for critical limb ischaemia: Biomimetic PLGA microcarriers potentiates the pro-angiogenic effect of adipose tissue stromal vascular fraction cells

Abstract: We propose a regenerative solution in the treatment of critical limb ischaemia (CLI). Poly-lactic/glycolic acid microcarriers were prepared and coated with laminin to be sterilized through γ-irradiation of 25 kGy at low temperature. Stromal vascular fraction (SVF) cells were extracted through enzymatic digestion of adipose tissue. Streptozotocin-induced diabetic mice underwent arteriotomy and received an administration of SVF cells combined or not with biomimetic microcarriers. Functional evaluation of the isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In our previous studies, we observed that nanofibrillar scaffolds had increased the survival duration of endothelial cells, and this potentially also applies to other cell types such as SVF cells ( Huang et al, 2013b ; Nakayama et al, 2015 ). It is plausible that the nanofibrillar scaffold prolonged the survival of SVF cells, resulting in a longer duration of therapeutic effect ( Hoareau et al, 2018 ). Besides VEGF, other interesting cellular signaling mechanisms may also be at play.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we observed that nanofibrillar scaffolds had increased the survival duration of endothelial cells, and this potentially also applies to other cell types such as SVF cells ( Huang et al, 2013b ; Nakayama et al, 2015 ). It is plausible that the nanofibrillar scaffold prolonged the survival of SVF cells, resulting in a longer duration of therapeutic effect ( Hoareau et al, 2018 ). Besides VEGF, other interesting cellular signaling mechanisms may also be at play.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments have demonstrated that a laminin-coated PLGA nerve catheter can not only promote the generation of sciatic nerve fibers [ 12 ], but it may also incorporate growth factors and adipogenic stem cells that promote the regeneration and functional recovery of the sciatic nerve [ 138 ]. In addition, Hoareau et al [ 139 ] used a laminin-coated PLGA microcarrier to deliver stromal vascular fraction (SVF) cells to the ischemic limb of a diabetic mouse model. The results showed that the delivering of cells via a microcarrier was more beneficial in terms of improving blood flow, reducing necrosis, and restoring limb sensation than injecting cells alone.…”
Section: Plga Scaffold Surface-modified Materialsmentioning
confidence: 99%